SINDROM TOLOSA HUNT DENGAN KETERLIBATAN SARAF OPTIKUS - Astra Dea Simanungkalit,* Maria Larasati Susyono,** Vivien Puspitasari* (Neurona Majalah Kedokteran Neuro Sains, 2019)
HUNT SYNDROME THS IS A VERY RARE CLINICAL SYNDROME WHICH IS CHARACTERIZED BY UNILATERAL HEADACHES ACCOMPANIED BY DYSFUNCTION AND PAINFUL OPHTHALMIC NERVES IN SOME CASES OPTIC NERVE INVOLVEMENT CAN BE FOUND DUE TO INFLAMMATION AT THE ORBITAL APEX